2009
DOI: 10.15666/aeer/0704_303318
|View full text |Cite
|
Sign up to set email alerts
|

Community Composition and Tree Population Structure in Undisturbed and Disturbed Tropical Semi-Evergreen Forest Stands of North-East India

Abstract: Lalfakawma et al.: Community composition and tree population structure in undisturbed and disturbed tropical semi- Abstract Species composition, density, importance value index, diversity, dominance and tree population structure were studied in disturbed and undisturbed stands of tropical semi-evergreen forest in Lunglei District of Mizoram, North-East India. Total number of species in the undisturbed stand was 67 while in the disturbed stand 63 species were recorded. Number of tree and shrub species in the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 56 publications
5
11
0
Order By: Relevance
“…Our result also agree with a study done by Lalfakawma et al (2009) whereby undisturbed stand showed higher species diversity as compared to disturbed stands. The low woody species diversity obtained from the production zone could be due to the excessive wood harvesting practice exhibited by the local community; as evidenced we visualized charcoal burning activities carried out in this zone (personal observation).…”
Section: Discussionsupporting
confidence: 93%
“…Our result also agree with a study done by Lalfakawma et al (2009) whereby undisturbed stand showed higher species diversity as compared to disturbed stands. The low woody species diversity obtained from the production zone could be due to the excessive wood harvesting practice exhibited by the local community; as evidenced we visualized charcoal burning activities carried out in this zone (personal observation).…”
Section: Discussionsupporting
confidence: 93%
“…The results therefore show that community composition and structure in the respective plots change with anthropogenic disturbance. This is consistent with the findings of Lalfakawma et al, (2009) that community composition changes with disturbance. The differences in vegetation characteristics between the 3-year fallow and abandoned farmland indicate that the continuous cultivation of land for food crop cultivation results in the alteration of the forest vegetation.…”
Section: Resultssupporting
confidence: 93%
“…The concentration of dominance (Simpson's index) in the present study is within the reported range 0.21-1.0 for tropical forests by several workers (Kumar et al 2010;Visalakshi 1995;Sahu et al 2012c). The evenness index values fall within the range between 0.64-1.34 in other forests (Lalfakwma et al 2009;Sahu et al 2012a). The Margalef richness index also within the range of 4.54-23.41 for other tropical forests (Mishra et al 2005;Kumar et al 2010).…”
Section: Discussionsupporting
confidence: 88%